Quantitative screening of the pharmaceutical ingredient for the rapid identification of substandard and falsified medicines using reflectance infrared spectroscopy - Lawson, Graham; Ogwu, John; Tanna, Sangeeta (PLOS ONE, 2018)
The World Health Organization suggests that approximately 10% of medicines worldwide are either falsified or substandard with higher figures in low and middle income countries. Such poor quality medicines can seriously harm patients and pose a threat to the economy worldwide. This study investigates attenuated total reflectance-fourier transform infrared (ATR-FTIR) spectroscopy as a simple and rapid method for determination of drug content in tablet dosage forms. Paracetamol was used as the model pharmaceutical ingredient. Spectra of standard mixtures of paracetamol with different excipients formed the basis for multivariate PLS based quantitative analysis of simulated tablet content using different selected infrared absorbance bands. Calibration methods using ATR-FTIR were compared with the ATR-FTIR and conventional ultraviolet spectroscopic analyses of real tablet samples and showed that the paracetamol/microcrystalline cellulose mixtures gave optimum results for all spectral bands tested. The quantitative data for band 1524–1493cm-1 was linear (R2 ˃ 0.98; LOQ ≥ 10%w/w tablet). Global examples of paracetamol tablets were tested using this protocol and 12% of the tablet samples examined was identified as substandard. Each sample analysis was completed in just a few minutes. ATR-FTIR can therefore be used in the rapid screening of tablet formulations. The simplicity of the proposed method makes it appropriate for use in low and middle income countries where analytical facilities are not available.